Ischemic stroke following COVID-19 vaccination - Nooshin Masoudian; Maryam Kakovan; Samaneh Ghorbani Shirkouhi; Fatemeh Ehsani; Sasan Andalib (Journal of Research in Clinical Medicine, 2023)
Following the coronavirus disease 2019 (COVID-19) vaccination, complications are expected. In this regard, coagulopathy after COVID-19 vaccination has been reported. Here, we report a rare case of ischemic stroke subsequent to receiving the Beijing Bio-Institute of Biological Products - Coronavirus (BBIBP-CorV) vaccine (Sinopharm). Ten days after receiving the first dose of the BBIBP-CorV vaccine, a 76-year-old woman showed right central hemifacial weakness, balance disorder, and right hemisensory involvement with normal muscle force. Although the magnetic resonance imaging assessment revealed an acute lacunar stroke in her left thalamus, laboratory findings were normal. Based on our report, ischemic stroke may be a post-complication of BBIBP- CorV vaccination. However, further studies are needed to confirm this finding.